Treatment of endometreiosis: Changing trends in management - U Nagashree; Sumana Manohar; R Charumathi (Apollo Medicine)
Endometriosis is one of the most common gynecological disease affecting 6-10% of women of reproductive age. There is no cure for endometriosis-except a few methods of reducing the symptoms; both medical and surgical. Prolonged medical treatments to suppress the symptoms alone is not beneficial. The transformation of endometriosis to malignancy is always a possibility and the need for proper follow up and complete surgical clearance should be explained to the patient.